Subjects of rights classification facing genomic and proteomic development - Varsi Rospigliosi, Enrique (Acta Bioethica, 2017)
Law categorizes human life according to its situation in society with the goal to provide adequate safety. The theory of the subject of rights is based on the juridical conceptualization of human life. As theory, it was created to recognize a real and effective legal regulation to human relations in society, taking into account that human life has many ways to appear in society. Life is one, but –be biological or social- it adopts diverse stages which deserves regulation according to their status. This essence and way in which life is presented allows its juridical categorization by the subject of rights theory. In this way, human life is regulated in its true essence and dimension; nevertheless, genomic and proteomic biotechnology have being altering their classic taxonomy, changing it when presenting new actors in a world of relations.